Abnormal Habituation of the Auditory Event-Related Potential P2 Component in Patients With Schizophrenia - Mazer, Prune; Macedo, Inês; Paiva, Tiago O.; Ferreira-Santos, Fernando; Pasion, Rita; Barbosa, Fernando; Almeida, Pedro; Silveira, Celeste; Cunha-Reis, Cassilda; Marques-Teixeira, João (Frontiers in Psychiatry, 2021)
Auditory event-related potentials (ERP) may serve as diagnostic tools for schizophrenia and inform on the susceptibility for this condition. Particularly, the examination of N1 and P2 components of the auditory ERP may shed light on the impairments of information processing streams in schizophrenia. However, the habituation properties (i.e., decreasing amplitude with the repeated presentation of an auditory stimulus) of these components remain poorly studied compared to other auditory ERPs. Therefore, the current study used a roving paradigm to assess the modulation and habituation of N1 and P2 to simple (pure tones) and complex sounds (human voices and bird songs) in 26 first-episode patients with schizophrenia and 27 healthy participants. To explore the habituation properties of these ERPs, we measured the decrease in amplitude over a train of seven repetitions of the same stimulus (either bird songs or human voices). We observed that, for human voices, N1 and P2 amplitudes decreased linearly from stimulus 1–7, in both groups. Regarding bird songs, only the P2 component showed a decreased amplitude with stimulus presentation, exclusively in the control group. This suggests that patients did not show a fading of neural responses to repeated bird songs, reflecting abnormal habituation to this stimulus. This could reflect the inability to inhibit irrelevant or redundant information at later stages of auditory processing. In turn schizophrenia patients appear to have a preserved auditory processing of human voices.